2012
DOI: 10.4319/lo.2012.57.2.0486
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dynamics and biological consumption in a large continental shelf system under the influence of both a river plume and coastal upwelling

Abstract: We examined the dynamics of dissolved inorganic nitrogen (DIN, nitrate + nitrite), dissolved inorganic phosphorus (DIP), and silicate (Si(OH) 4 ) in the northern shelf of the South China Sea in summer, which is under a complex hydrodynamic scheme largely shaped by river plume and coastal upwelling, along with the enhanced biological consumption of nutrients therein. The Pearl River plume, with high nutrient concentrations (, 0.1-14.2 mmol L 21 for DIN, , 0.02-0.10 mmol L 21 for DIP, and , 0.2-18.9 mmol L 21 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
185
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 188 publications
(190 citation statements)
references
References 32 publications
5
185
0
Order By: Relevance
“…Plots of temperature-normalized pCO 2 versus salinity (Fig. 10a) revealed that many of those summer data were associated with an estuarine plume (with a salinity of less than 33), where biological productivity was enhanced in the surface water due to nutrient support from the eutrophicated PRE (Cao et al, 2011;Han et al, 2012). Dai et al (2008), Zhai et al (2009), andCao et al (2011) have shown that the Pearl River plume can serve as a CO 2 sink.…”
Section: Factors Influencing Sea Surface Pcomentioning
confidence: 99%
See 1 more Smart Citation
“…Plots of temperature-normalized pCO 2 versus salinity (Fig. 10a) revealed that many of those summer data were associated with an estuarine plume (with a salinity of less than 33), where biological productivity was enhanced in the surface water due to nutrient support from the eutrophicated PRE (Cao et al, 2011;Han et al, 2012). Dai et al (2008), Zhai et al (2009), andCao et al (2011) have shown that the Pearl River plume can serve as a CO 2 sink.…”
Section: Factors Influencing Sea Surface Pcomentioning
confidence: 99%
“…We considered four contrasting physical-biogeochemical domains, and were able to significantly improve our understanding regarding the spatial variability of CO 2 fluxes. Among these four domains, A was adjacent to the Pearl River estuary (PRE) and was thus influenced by the summer estuarine plume (Gan et al, 2009;Cao et al, 2010;Han et al, 2012). Domain B covered the slope and deep basin areas in the northern SCS, which is typically oligotrophic and low in productivity .…”
Section: W-d Zhai Et Al: Seasonal Variations Of Sea-air Co 2 Fluxementioning
confidence: 99%
“…1a; Table 1 Samples were collected close to the south of the Taiwan Strait, which is located in the northeastern part of the SCS, during the cruises in August 2003 (ORIII-896) and July 2004 (ORIII-983). ORI-695 was conducted near the Pearl River estuary and was influenced by the summer estuarine plume (Gan et al, 2009;Cao et al, 2011;Han et al, 2012;Zhai et al, 2013;Bai et al, 2015). The Pearl River (Zhujiang) is the 13th largest river in the world (Yin et al, 2004) and the second largest river in China (after the Yangtze River) with a water discharge of 326 Â 10 9 m 3 annually; it is also the second largest river (after the Mekong River) that enters the SCS (Chen et al, 2008).…”
Section: Sample Collectionsmentioning
confidence: 99%
“…The Pearl River, as the largest river draining into the nSCS, carries the considerable loads of anthropogenic nutrients (Han et al 2012). The nSCS has an extensive continental shelf with a variable offshore extension along the southern coasts of China.…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%